Synthesis of pure intermetallic phases on the example of the ternary phase τ1 in the system Al-Fe-Ni. (February 2019) - Lippmann, Stephanie; Kemsies, Richard H.; Schick, Michael; Milkereit, Benjamin; Kessler, Olaf; Rettenmayr, Markus; Hack, Klaus
Abstract: An experimental method for the synthesis of the ternary τ1 Al9 (Fe, Ni)2 phase in the Al-Fe-Ni system in quantities of up to several grams is presented. The resolidification of the mushy zone in a stationary temperature gradient is employed. In a temperature gradient, solidifying phases may form spatially separated in a sequence following the two-phase equilibria liquid/solid in the equilibrium phase diagram. An initial composition different from that of the desired intermetallic phase needs to be chosen. A suitable concentration for synthesizing τ1 was identified on the basis of a preliminary ternary phase diagram in combination with solid/liquid coarsening experiments. After confirmation of the single-phase state of τ1 using XRD, the heat capacity of τ1 was measured, and the thermodynamic description of τ1 was re-assessed. The Neumann-Kopp rule that is frequently employed for the thermodynamic description of the heat capacity is found to be inadequate in the case of τ1, and the problem appears to be of some generality. Highlights: Research highlights: Introduction of an experimental method for synthesizing pure, bulk intermetallic phases. Measurement of the heat capacity of the ternary τ1 Al9 (Fe, Ni)2 phase. Analysis of phase stabilities on the Al-rich side in Al-Fe-Ni system.